Taslica-Mersincik. A Multicultural Meeting Point - Kizilduman, Bülent; Öğmen, Seren S. (Mersin University, 2022)
In the course of a survey carried out on the borders of Taşlıca village in the Karpas Peninsula a new archaeological site was recorded. To evaluate the historical role of the area, work at Taşlıca was carried out with special care and was named Taşlıca-Mersincik in the literature. The limits of the archaeological site and its chronology were determined. Within the site which will be declared to the scientific world as Taşlıca-Mersincik, pottery, fragments and unfinished statues, as well as architectural stone sculpture and structural pieces were identified. Among the many finds is a select group consisting of 24 statue fragments, carved stone, and terracotta fragments. Together with diagnostic pottery from the surface they were used for a chronological comparison with other sites. The great majority of the Taşlıca-Mersincik pottery, consisting of coarse ware and vessels for everyday use, belongs to Cypro-Archaic II. The existence of a very small number of pieces of Late Roman date demonstrated the existence of a later occupation as well, but no continuous settlement. Ceramic cinders retrieved within the area, might point to pottery production or ritual activities at the site. The sculptural fragments show both domestic and foreign characteristics and belong to the second half of the Archaic II phase. They indicate a possible sculpture work-shop showing international influences. The location of the site close to important straits and harbour areas, as well as the multicultural nature of the artefacts hints at overseas contacts and a possible harbour site at the coast. As a result of the survey at Taşlıca-Mersincik, information concerning the sociocultural and economic life of the settlement was recorded. Thus, it is likely that, as a result of future stratigraphical excavation, the role of the settlement, as well as that of the Karpas Peninsula, within the eastern Mediterranean networks might become much clearer. © 2022 Mersin University. All rights reserved.
TAŞLICA-MERSÎNCİK. A MULTICULTURAL MEETING POINT
Keywords: Archaic; Cyprus; Harbor; Location; Multicultural; Statue